Precursor of lithium battery positive electrode material, its preparation method and its application

A lithium battery positive electrode active material precursor with a unique morphology of plate-like and polyhedral single crystals, synthesized via intermittent metal salt solution supply, addresses electrochemical property issues, achieving high discharge capacity and stability.

JP7601866B2Active Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022522945
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-17
Filing Date
2020-10-16
Publication Date
2024-12-17
Estimated Expiration
2040-10-16

AI Technical Summary

Technical Problem

Existing lithium-ion battery cathode active materials face issues with morphology affecting electrochemical properties, leading to poor cycling stability and capacity due to side reactions between small polycrystalline particles and electrolyte, and large dispersed single crystals having poor capacity and output characteristics.

Method used

Development of a lithium battery positive electrode active material precursor comprising an aggregate of plate-like single crystals and polyhedral single crystal particles, with specific X-ray diffraction intensity ratios, formed through a method involving intermittent supply of a metal salt solution during synthesis.

Benefits of technology

The precursor material exhibits improved electrochemical properties, including high discharge capacity, good cycle stability, and efficient first cycle efficiency, with discharge capacities up to 206.9 mAh/g and capacity retention rates of 96.1% after 80 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601866000007
    Figure 0007601866000007
  • Figure 0007601866000008
    Figure 0007601866000008
  • Figure 0007601866000009
    Figure 0007601866000009
Patent Text Reader

Abstract

A precursor for a lithium battery cathode active material, a method for preparing the same, and uses thereof are disclosed. The precursor is Ni x Co y M z (OH)2, where M is at least one metal selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al, and 0.3≦x≦1, 0
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS] This application claims priority to Chinese Patent Application No. 201910990467.8, filed on October 17, 2019, entitled "Positive electrode active material precursor, preparation method thereof, positive electrode active material, and application thereof," and Chinese Patent Application No. 201910989951.9, filed on October 17, 2019, entitled "Positive electrode active material precursor, preparation method thereof, lithium battery positive electrode, and application thereof," the entire contents of which are incorporated herein by reference. [Technical field] The present application relates to the field of lithium batteries, and in particular to lithium battery positive electrode active material precursors, their preparation, and applications. [Background technology] Lithium ion batteries (also referred to as "lithium batteries" in this application) have advantages such as high energy density, high output voltage, low self-discharge, excellent cycle performance, no memory effect, etc., and are widely used in the fields of portable electronic products, power tools, electric vehicles, etc. Particularly in recent years, the promotion policies of new energy vehicles by governments of various countries have been continuously upgraded, promoting the rapid development of lithium batteries for power generation.

[0002] The positive electrode active material is a key component of lithium batteries, which not only determines key indicators such as the energy density of lithium batteries, but also accounts for about 40% of the overall battery cost. With the demand for improved mileage of electric vehicles, ternary positive electrode active materials with higher energy density are gradually becoming the mainstream positive electrode active materials for passenger cars.

[0003] The morphology of a lithium battery positive electrode active material has a significant effect on its electrochemical properties. Currently, there are two main morphologies of commercially available ternary positive electrode active materials. The first morphology is a micron-scale spherical secondary polycrystalline aggregate particle formed by the aggregation of nano-scale or submicron-scale primary particles. The small polycrystalline particles of a positive electrode active material with this morphology can be in full contact with the electrolyte to provide good output characteristics, but side reactions between the small polycrystalline particles and the electrolyte can easily occur, causing the transition metal to dissolve in the electrolyte, and therefore exhibiting poor battery cycle stability. The other morphology is a dispersed single crystal particle. A positive electrode active material with this morphology has a stable crystal structure, good compatibility with the electrolyte during charging and discharging, is not easily broken during cycling, and exhibits good battery cycle stability, but the dispersed single crystal particles are large and have poor capacity and output characteristics.

[0004] For ternary positive electrode active materials, their morphology is substantially determined by their precursors. At present, the morphology of commercially available ternary positive electrode active material precursors is mainly micron-scale spherical secondary polycrystalline aggregate particles formed by the aggregation of nano- or submicron-scale primary particles. For example, China Patent Application Publication No. 107915263A discloses a precursor having a micron-scale spherical secondary polycrystalline aggregate morphology with a particle size of 3.5-4.0 μm. During the charge and discharge process, the fine primary particles of such materials may come into contact with and react with the electrolyte, so that the capacity and primary cycle efficiency of the polycrystalline material are relatively low, which does not meet the requirements for practical application in power batteries. [Summary of the Invention] In order to overcome the problems suffered in the prior art, it is an object of the present application to provide a novel precursor of a lithium battery cathode active material, its preparation, its application, and a lithium battery cathode active material prepared from this precursor, which exhibits improved electrochemical properties.

[0005] In order to achieve the above object, in one aspect, the present application provides a precursor for a lithium battery positive electrode active material, comprising: Chemical formula Ni x Co y M zIt has (OH)₂, M is at least one metal selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al, 0.3 ≦ x ≦ 1, 0 < y ≦ 0.5, 0 < z ≦ 0.3, and the values of x, y, and z satisfy the principle of electrical neutrality. The precursor includes an aggregate of plate-like single crystals and polyhedral single crystal particles. I(001), I(100), and I(101) of the X-ray diffraction pattern of the precursor are such that I(001) / I(100) is about 1.5 or more, and I(001) / I(101) is about 1.2 or more. It satisfies the relationship. Preferably, I(101) / I(100) is about 1.3 or more. I(001), I(100), and I(101) respectively represent the intensities at the peak heights of the diffraction peaks corresponding to the (001) crystal plane, (100) crystal plane, and (101) crystal plane. It provides a precursor of a lithium battery cathode active material.

[0006] In another aspect, the present application is a method for preparing a precursor of a lithium battery cathode active material, comprising: (1) A step of mixing a metal salt solution with a precipitating agent solution and a complexing agent solution and reacting them, wherein while continuously supplying the precipitating agent solution and the complexing agent solution to the reaction system, intermittently supplying the metal salt solution to the reaction system; (2) A step of subjecting the product obtained in step (1) to solid-liquid separation and drying treatment to obtain the precursor. It includes The metal in the metal salt solution includes Ni, Co, and M. The metal M is at least one selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al. The molar ratio of the metals Ni, Co, and M is about (0.3 - 1):(0 - 0.5):(0 - 0.3). The molar amounts of Co and M used are not zero. It provides a preparation method.

[0007] In another aspect, the present application provides a precursor of a lithium battery positive electrode active material obtained by the method of preparing a precursor of a lithium battery positive electrode active material according to the present application.

[0008] In another aspect, the present application provides a lithium battery cathode active material, comprising: Li a Ni x Co y M z It has the chemical formula of O2, M is at least one metal selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al; 0.9≦a≦1.2, 0.3≦x≦1, 0 <y≦0.5、0<z≦0.3であり、 The values ​​of a, x, y, and z satisfy the electroneutrality law, The positive electrode active material includes particles in the form of secondary fusions of single crystals formed by at least partially fused primary single crystal particles. A lithium battery positive electrode active material is provided.

[0009] In another aspect, the present application relates to: A method for producing a lithium battery positive electrode active material, comprising the steps of: (I) preparing a precursor of a lithium battery positive active material; (II) mixing the precursor with a lithium source to cause a solid-state reaction to obtain a positive electrode active material; Including, The precursor is a lithium battery positive electrode active material precursor according to the present application, Methods of manufacture are provided.

[0010] In another aspect, the present application provides a lithium battery positive electrode active material obtainable by the method for producing a lithium battery positive electrode active material according to the present application.

[0011] In yet another aspect, the present application provides a lithium battery cathode comprising a cathode active material, a binder, and a conductive additive, wherein the cathode active material is the lithium battery cathode active material of the present application.

[0012] In yet another aspect, the present application provides a lithium battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the positive electrode is a lithium battery positive electrode according to the present application.

[0013] The lithium battery cathode active material precursor according to the present application, unlike a ternary cathode active material precursor having a spherical polycrystalline aggregate morphology, comprises an aggregate of plate-like single crystals and polyhedral single crystal particles and has a larger exposed area of ​​(001) and (101) crystal faces, and therefore the cathode active material precursor exhibits improved electrochemical properties.

[0014] The lithium battery cathode active material according to the present application, unlike existing cathode active materials in the form of spherical polycrystalline aggregates and dispersed single crystal particles, comprises particles in the form of secondary fusion of single crystals formed by at least partially fused primary single crystal particles. The cathode active material has both the advantages of a ternary cathode active material having a spherical polycrystalline aggregate morphology and the advantages of a ternary cathode active material having a dispersed single crystal morphology, and exhibits high discharge capacity, high first cycle efficiency, good power characteristics and good cycle stability characteristics. A lithium battery fabricated using the cathode active material may exhibit a discharge capacity of 206.9 mAh / g, a first cycle efficiency of 92.1%, a capacity retention of 96.1% after 80 cycles at a rate of 0.1 C, and a discharge capacity of 120 mAh / g at a rate of 10 C. [Brief description of the drawings] FIG. 1A is an SEM image of the positive electrode active material precursor obtained in Example 1 of the present application.

[0015] FIG. 1B is an SEM image of the positive electrode active material precursor obtained in Example 1 of the present application.

[0016] FIG. 2 shows the X-ray diffraction pattern of the positive electrode active material precursor obtained in Example 1 of the present application.

[0017] FIG. 3A is an SEM image of the positive electrode active material obtained in Example 1 of the present application.

[0018] FIG. 3B is an SEM image of the positive electrode active material obtained in Example 1 of the present application.

[0019] FIG. 3C is a TEM image of the positive electrode active material obtained in Example 1 of the present application.

[0020] FIG. 3D is an SEM image of a cross section of the positive electrode active material obtained in Example 1 of the present application.

[0021] FIG. 4 shows the X-ray diffraction pattern of the positive electrode active material obtained in Example 1 of the present application.

[0022] FIG. 5 shows the charge / discharge curve of a lithium battery assembled using the positive electrode active material of Example 1 of the present application, measured at a rate of 0.1 C.

[0023] FIG. 6 shows the cycle capacity retention curve of a lithium battery assembled using the positive electrode active material of Example 1 of the present application, measured at a rate of 0.1C.

[0024] FIG. 7 shows the capacity results measured at various rates for a lithium battery assembled using the positive electrode active material of Example 1 of the present application.

[0025] FIG. 8 is an SEM image of the positive electrode active material precursor obtained in Comparative Example 1 of the present application.

[0026] FIG. 9 shows an X-ray diffraction pattern of the positive electrode active material precursor obtained in Comparative Example 1 of the present application.

[0027] FIG. 10A is an SEM image of the positive electrode active material obtained in Comparative Example 1 of the present application.

[0028] FIG. 10B is a TEM image of the positive electrode active material obtained in Comparative Example 1 of the present application.

[0029] FIG. 11 shows the results of the capacity measured at various ratios of a lithium battery assembled using the positive electrode active material of Comparative Example 1 of the present application. [Explanation of symbols] A Aggregate of plate-like single crystals B Polyhedral single crystal particles [Detailed Description of the Invention] The present application will now be described in more detail with reference to specific embodiments thereof and the accompanying drawings. It should be noted that the specific embodiments of the present application are provided for illustrative purposes only and are not intended to be limiting in any manner.

[0030] Any specific numerical value, including the end point of a numerical range, described in the context of this application should not be limited to that exact value, but should be interpreted as further embracing all values ​​close to said exact value.Furthermore, with respect to any numerical range described herein, any combination between the end points of the range, between each end point and any specific value within the range, or between any two specific values ​​within the range, can be made to provide one or more new numerical ranges, in which case said new numerical ranges should also be considered as specifically described in this application.

[0031] Unless otherwise specified, terms used herein have the same meaning as commonly understood by one of ordinary skill in the art, and where terms are defined herein and those definitions differ from the normal understanding in the art, the definitions provided herein shall control.

[0032] In the context of the present application, the expression "fulfilling / fulfilling the principle of electroneutrality" means that the algebraic sum of the valences of all elements present in the corresponding chemical formula is zero.

[0033] In the context of this application, the term "agglomerate" refers to an aggregate formed by multiple particles that are clumped together by physical interactions (e.g., electrostatic forces, van der Waals forces, etc.) The aggregates can be easily broken down by external forces since the interactions between the multiple particles are weak.

[0034] In the context of this application, the term "fusion body" refers to an ordered structure formed by at least partially fusing and bonding multiple particles. The fusion body cannot be easily broken down by external forces because multiple particles are fused together into a single body.

[0035] In the context of this application, the expression "at least partially fused / fused" means that at least a portion of the body of a particle is fused with at least a portion of the body of another particle, thereby forming a single body.

[0036] In the context of the present application, the expression "intermittently feeding / feeding" means that the metal salt solution is discontinuously fed to the reaction system in multiple (in examples, 2, 3, 4, 5, 6, etc.) portions, preferably in a continuous manner, in particular at a constant rate, until each portion reaches a predetermined point in time or a predetermined amount of material has been added.

[0037] In the context of this application, in addition to the subject matter explicitly described, the subject matter not described shall be considered to be the same as that known in the art without any changes. Moreover, any of the embodiments described herein may be freely combined with one or more other embodiments described herein, and the technical solutions or concepts thus obtained shall be considered as part of the original disclosure or original description of this application, and shall not be considered as new matters not disclosed or anticipated herein, unless it is obvious to a person skilled in the art that such combination is obviously unreasonable.

[0038] All publications, patent applications, patents, and other references cited herein are incorporated by reference in their entirety.

[0039] In a first aspect, the present application provides a method for producing a method for manufacturing a semiconductor device comprising: A precursor of a lithium battery positive electrode active material, It contains aggregates of plate-like single crystals and polyhedral single crystal particles, The X-ray diffraction patterns of the precursor are I(001), I(100), and I(101). I(001) / I(100) is about 1.5 or more, preferably about 10 or less, and I(001) / I(101) is about 1.2 or more, preferably about 5 or less; Fulfilling relationships, Preferably, I(101) / I(100) is greater than or equal to about 1.3, and preferably less than or equal to about 5; The precursor is Ni x Co y M z It has the chemical formula (OH) M is at least one metal selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al; 0.3≦x≦1, 0 <y≦0.5、0<z≦0.3であり、 The values ​​of x, y, and z satisfy the electroneutrality law. A precursor is provided.

[0040] According to the present application, the precursor comprises an aggregate of plate-like single crystals and polyhedral single crystal particles, and preferably, the precursor consists essentially of an aggregate of plate-like single crystals and polyhedral single crystal particles.

[0041] In the context of this application, the term "aggregates of plate-like single crystals" refers to particles having a primary morphology of plate-like single crystals and a secondary morphology of aggregates formed by aggregation of plate-like single crystals, and the term "polyhedral single crystal particles" refers to single crystal particles having a polyhedral morphology.

[0042] In the context of this application, I(001) refers to the intensity of the diffraction peak corresponding to the (001) crystal plane, I(100) refers to the intensity of the diffraction peak corresponding to the (100) crystal plane and I(101) refers to the intensity of the diffraction peak corresponding to the (101) crystal plane, the intensity of said diffraction peak being measured as its height.

[0043] In some preferred embodiments, the X-ray diffraction pattern of the precursor has I(001), I(100), and I(101) I(001) / I(100) is about 1.5 or more and about 10 or less, for example, about 5 or less or about 3 or less; I(001) / I(101) is about 1.2 or more and about 5 or less, for example, about 3 or less or about 2 or less, and I(101) / I(100) is about 1.3 or more and about 5 or less, for example, about 3 or less or about 2 or less; Fulfilling relationships.

[0044] In some preferred embodiments, the I(001), I(100), and I(101) in the X-ray diffraction pattern of the precursor satisfy the following relationships: I(001) / I(100) is about 1.8 or more, I(001) / I(101) is about 1.3 or more, and I(101) / I(100) is about 1.5 or more.

[0045] In a particularly preferred embodiment, the I(001), I(100), and I(101) in the X-ray diffraction pattern of the precursor satisfy the relationship that I(001) / I(100) is about 1.8 or more and about 10 or less, for example, about 5 or less or about 3 or less, I(001) / I(101) is about 1.3 or more and about 5 or less, for example, about 3 or less or about 2 or less, and I(101) / I(100) is about 1.5 or more and about 5 or less, for example, about 3 or less or about 2 or less.

[0046] In a preferred embodiment, in the chemical formula of the precursor, 0.6≦x≦0.95, 0.025≦y≦0.2, and 0.025≦z≦0.2.

[0047] In a preferred embodiment, M is at least one of Mn, Al, and Mg, or a combination of at least one of Mn, Al, and Mg with at least one selected from the group consisting of Fe, Cr, Cu, Ti, W, Mo, Nb, Zn, Sn, Zr, and Ga. For example, the precursor has the formula Ni x Co y Mn z(OH)2, Ni x Co y Al z (OH)2 or Ni x Co y Mg z (OH)2, where x, y, and z are as defined above.

[0048] In a preferred embodiment of the present application, the SEM images of the precursor may be as shown in Figures 1A and 1B. As can be seen from Figures 1A and 1B, the precursor of the lithium battery positive electrode active material of the present application comprises an aggregate of plate-like single crystals and polyhedral single crystal particles. As can be seen from Figure 2, the precursor of the positive electrode active material has at least three diffraction peaks, including a (001) diffraction peak at 2θ of about 19.6°, a (100) diffraction peak at 2θ of about 33.4°, and a (101) diffraction peak at 2θ of about 38.8°. The diffraction peaks of the precursor are sharp, indicating that the crystal structure of the precursor is well developed. The intensities of the diffraction peaks corresponding to the (001) and (101) crystal planes are relatively high, indicating that the (001) and (101) crystal planes of the precursor, especially the (001) crystal plane, are more exposed. The precursor of the lithium battery cathode active material is significantly different from existing cathode active material precursors having a spherical polycrystalline aggregate morphology. The spherical polycrystalline aggregates in the existing precursors exhibit a spherical or globular morphology, and the intensities of their diffraction peaks (especially the intensities of the (001) crystallographic plane and / or the (101) crystallographic plane) are significantly lower than those of the precursor of the present application.

[0049] In the present application, the particle size (D50) of the positive electrode active material precursor is preferably 2 μm to 12 μm, as measured by dynamic light scattering.

[0050] In a second aspect, the present application provides a method for producing a method for manufacturing a semiconductor device comprising: A method for producing a precursor of a lithium battery positive electrode active material, comprising the steps of: (1) a step of mixing a metal salt solution with a precipitant solution and a complexing agent solution to react with each other, the step of intermittently supplying the metal salt solution to a reaction system while continuously supplying the precipitant solution and the complexing agent solution to the reaction system; (2) subjecting the product obtained in the step (1) to solid-liquid separation and drying to obtain a positive electrode active material precursor; Including, The metals in the metal salt solution include Ni, Co, and M, where M is at least one selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al, the molar ratio of Ni, Co, and M is about (0.3-1):(0-0.5):(0-0.3), and the molar amounts of Co and M used are not zero.

[0051] The present inventors have unexpectedly found that, in the preparation of a precursor for a lithium battery positive electrode active material, a precursor obtained by continuously supplying a starting material typically exhibits a spherical polycrystalline aggregate morphology, but by intermittently supplying a metal salt solution, a precursor containing an aggregate of plate-like single crystals and polyhedral single crystal particles is obtained, and the precursor having such a special morphology exhibits improved electrochemical properties.

[0052] In a preferred embodiment, the molar ratio of Ni, Co, and M in the metal salt solution is about (0.6-0.95):(0.025-0.2):(0.025-0.2).

[0053] In the present application, the metal salt solution may be any metal salt solution conventionally used in the art for preparing lithium battery cathode active materials or cathode active material precursors. Preferably, the metal M is at least one of Mn, Al, and Mg, or a combination of at least one of Mn, Al, and Mg with at least one selected from the group consisting of Fe, Cr, Cu, Ti, W, Mo, Nb, Zn, Sn, Zr, and Ga. For example, the metal in the metal salt solution may be a combination of Ni, Co, and Mn, a combination of Ni, Co, and Al, or a combination of Ni, Co, and Mg.

[0054] In the present application, the type of the metal salt constituting the metal salt solution is not particularly limited. Preferably, the metal salt is at least one selected from the group consisting of sulfates, nitrates, acetates, chlorides, and oxalates. For example, the salt of Ni may be at least one selected from nickel sulfate, nickel nitrate, nickel acetate, nickel oxalate, and nickel chloride. The salt of metal Co may be at least one selected from cobalt nitrate, cobalt chloride, cobalt acetate, and cobalt sulfate. The salt of metal Mn may be at least one selected from manganese sulfate, manganese nitrate, manganese acetate, and manganese chloride. The salt of Al may be at least one selected from aluminum nitrate, aluminum chloride, aluminum acetate, and aluminum sulfate. The salt of metal Mg may be at least one selected from magnesium nitrate, magnesium chloride, magnesium acetate, and magnesium sulfate.

[0055] In a preferred embodiment, the concentration of the metal salt solution, in terms of metal element, is about 0.0 to 5 mol / L, for example, about 0.01 mol / L, about 0.1 mol / L, about 0.5 mol / L, about 1 mol / L, about 2 mol / L, about 3 mol / L, about 4 mol / L, about 5 mol / L, or within a range formed between any two of these values, more preferably about 0.5 to 3 mol / L, even more preferably about 1 to 2 mol / L.

[0056] In the present application, the type of the precipitating agent is not particularly limited. Preferably, the precipitating agent is at least one selected from NaOH, KOH, and LiOH.

[0057] In the present application, the concentration of the precipitant solution is not particularly limited.Preferably, the concentration of the precipitant solution is about 0.02 to 10 mol / L, for example, about 0.02 mol / L, about 0.1 mol / L, about 0.5 mol / L, about 1 mol / L, about 2 mol / L, about 3 mol / L, about 4 mol / L, about 5 mol / L, about 6 mol / L, about 7 mol / L, about 8 mol / L, about 9 mol / L, and about 10 mol / L, or within a range formed between any two values ​​among these values, more preferably about 2 to 8 mol / L, and even more preferably about 2 to 6 mol / L.

[0058] In the present application, the type of the complexing agent is not particularly limited, and may be any compound capable of forming a complex with Ni, Co, and M in an aqueous solution. Preferably, the complexing agent is at least one selected from the group consisting of an ammonium ion donor, an ethanolamine complexing agent, an aminocarboxylic acid complexing agent, a hydroxyaminocarboxylic acid complexing agent, and a carboxylate complexing agent. For example, the ammonium ion donor is preferably at least one selected from the group consisting of aqueous ammonia, ammonium oxalate, ammonium carbonate, and ammonium hydroxide. The ethanolamine complexing agent is preferably diethanolamine. The aminocarboxylic acid complexing material is preferably at least one selected from trisodium nitrilotriacetate (NTA), ethylenediaminetetraacetic acid (EDTA) and its salts, and diethylenetriaminepentaacetic acid (DTPA). The hydroxyaminocarboxylic acid complexing agent is preferably at least one selected from the group consisting of hydroxyethylenediaminetetraacetic acid (HEDTA), ethylene glycol bis(β-diaminoethyl)ethyl ether-N,N,N'-tetraacetic acid (EGTA) and its salts, and dihydroxyglycine and its salts. The carboxylate complexing agent is preferably at least one selected from the group consisting of oxalic acid and its salts, tartaric acid and its salts, citric acid and its salts, gluconic acid and its salts, carboxymethylhydroxymalonic acid (CMOM) and its salts, carboxymethylhydroxysuccinic acid (CMOS) and its salts, and hydroxyethylglycine (DHEG) and its salts.

[0059] In the present application, the concentration of the complexing agent solution is not particularly limited.Preferably, the concentration of the complexing agent solution is about 0.01 to 15 mol / L, for example, about 0.01 mol / L, about 0.1 mol / L, about 0.5 mol / L, about 1 mol / L, about 2 mol / L, about 3 mol / L, about 4 mol / L, about 5 mol / L, about 6 mol / L, about 7 mol / L, about 8 mol / L, about 9 mol / L, about 10 mol / L, about 11 mol / L, about 12 mol / L, about 13 mol / L, about 14 mol / L, about 15 mol / L, or within a range formed between any two values ​​among these values, more preferably about 2 to 10 mol / L, and even more preferably about 2 to 6 mol / L.

[0060] According to the present application, in step (1), the reaction conditions preferably include a temperature of about 30-70°C, preferably about 45-60°C, a reaction time of about 10 hours or more, preferably about 24-72 hours, and a pH of about 9-14, preferably about 9-12, and the metal salt solution is supplied to the reaction system in at least two portions. By controlling the reaction temperature and / or time, the growth of the precursor crystals can be controlled.

[0061] In a preferred embodiment, the step (1) further comprises: (1a) continuously supplying the metal salt solution, the precipitant solution, and the complexing agent solution to a reactor and mixing and reacting them for about 2 to 12 hours, preferably about 3 to 8 hours; (1b) interrupting the supply of the metal salt solution for about 0.5 to 4 hours, preferably about 1 to 3 hours; (1c) repeating steps (1a) and (1b) until the reaction is completed.

[0062] In yet a further preferred embodiment, the duration of said step (1a) is not more than about 5 / 6, preferably not more than about 2 / 3, of the total time of said step (1).

[0063] According to the present application, in the step (1), the pH of the reaction system is controlled in the range of about 9 to 14, preferably in the range of about 9 to 12. In particular, in the step (1a), the pH of the reaction system is controlled in the range of about 9 to 12, preferably in the range of about 10 to 11.5.

[0064] In the present application, the amounts of the metal salt, the precipitating agent, and the complexing agent can be selected within a wide range, and the molar ratio of the metal salt, the precipitating agent, and the complexing agent can typically be about 1:(1.5-3):(0.5-6).

[0065] According to the present application, the supply rate of each reacting material may be selected within a wide range, as long as the supply rate is sufficient to maintain the pH of the reaction system in step (1), particularly step (1a), within a predetermined range. In general, the appropriate size of the reactor may be selected based on the total amount of reacting materials, and then the appropriate supply rate may be determined based on factors such as the reactor volume and reaction time, which can be easily determined by a person skilled in the art based on the present disclosure.

[0066] According to the present application, in the continuous supply stage of step (1) (e.g., step (1a)), the volume ratio of the supply rates of the metal salt solution and the complexing agent solution can generally be about 0.5 to 6, and the supply rate of the precipitating agent is controlled at a level sufficient to maintain the pH of the reaction system within a predetermined range.

[0067] In some preferred embodiments, the metal salt solution is supplied at a rate of about 10-200 mL / hr based on a total of 1 L of metal salt solution, the precipitant solution is supplied at a rate of about 10-200 mL / hr based on a total of 1 L of precipitant solution, and the complexing agent solution is supplied at a rate of about 10-200 mL / hr based on a total of 1 L of complexing agent solution. The supply rates can be controlled by one skilled in the art according to the required pH.

[0068] It should be noted that, based on a total of 1 L of metal salt solution, the supply rate of the metal salt solution is about 10 to 200 mL / hour, which means that when the capacity of the reactor is matched with the total amount of reacting materials, the supply rate of the metal salt solution is about 10 to 200 mL / hour per 1 L of the metal salt solution. For example, when the total amount of the metal salt solution is 0.5 L, the supply rate of the metal salt solution is about 5 to 100 mL / hour, and when the total amount of the metal salt solution is 5 L, the supply rate of the metal salt solution is about 50 to 1000 mL / hour.

[0069] In the present application, the method of supplying the reacting materials is not particularly limited, and the supply may be performed by any conventional method known in the art, for example, a dropwise method.

[0070] In a preferred embodiment, the mixing in step (1) is performed under stirring, and more preferably, the stirring speed is about 50 to 1000 r / min, for example, about 50 r / min, about 80 r / min, about 100 r / min, about 200 r / min, about 300 r / min, about 400 r / min, about 500 r / min, about 600 r / min, about 700 r / min, about 800 r / min, about 900 r / min, and about 1000 r / min, or within a range formed between any two values ​​among these values, more preferably about 600 to 1000 r / min.

[0071] In the present application, the product obtained in step (1) is preferably subjected to a cooling treatment before solid-liquid separation. After the cooling treatment, the temperature of the product is preferably lowered to room temperature, for example, about 25°C.

[0072] In the present application, the solid-liquid separation in step (2) may be carried out by any appropriate method as long as it can separate and remove the obtained precursor, and for example, filtration or centrifugation can be used.

[0073] In the present application, the product obtained by solid-liquid separation is preferably subjected to a washing treatment.

[0074] In the present application, the drying treatment in step (2) may be carried out by any conventional method in the art, such as vacuum drying, air drying, freeze drying or oven drying. The conditions of the drying treatment can be selected within a wide range, for example, about 70 to 150 °C and about 4 to 16 hours.

[0075] In a third aspect, the present application provides a precursor of a lithium battery cathode active material obtained by a method for preparing a precursor of a lithium battery cathode active material.

[0076] Since the characteristics of the precursor of the lithium battery cathode active material according to the third aspect of the present application are as described above in the first aspect of the present application, the description thereof is omitted here.

[0077] In a fourth aspect, the present application provides a lithium battery cathode active material comprising particles in the form of a single crystal secondary fusion body formed by at least partially fused primary single crystal particles, wherein the cathode active material has the chemical formula Li a Ni x Co y M z O2, where M is at least one metal selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al, 0.9 ≦ a ≦ 1.2, 0.3 ≦ x ≦ 1, 0 < y ≦ 0.5, 0 < z ≦ 0.3, and the values of a, x, y, and z satisfy the electrical neutrality rule. provides a lithium battery cathode active material.

[0078] According to the present application, the cathode active material comprises a plurality of particles in the form of a plurality of single crystal secondary fusion bodies formed by at least partially fused primary single crystal particles. Preferably, the cathode active material consists essentially of particles in the form of a plurality of single crystal secondary fusion bodies.

[0079] According to the present application, the term "primary single crystal particles" refers to the primary particles constituting the positive electrode active material. The primary single crystal particles generally have a polyhedral-like morphology, particularly a cubic-like morphology. Generally, the primary single crystal particles are not uniform in size, which helps to increase the tap density of the material. The term "secondary fusion of single crystals" refers to a fusion formed by at least partially fusing the above-mentioned primary single crystal particles. The secondary fusion of single crystals is usually formed by five or more primary single crystal particles. In some embodiments, the secondary fusion of single crystals exists as an irregularly shaped solid particle having a plurality of protrusions on its surface.

[0080] In a preferred embodiment, the positive electrode active material has a layered crystal structure.

[0081] In a preferred embodiment of the present application, the SEM images of the positive electrode active material are shown in FIG. 3A and FIG. 3B, and the particle morphology of the positive electrode active material is a secondary fusion of single crystals formed by at least partially fused primary single crystal particles. In particular, the primary single crystal particles have a cubic morphology and are not uniform in size, and five or more primary single crystal particles are fused to each other to form a secondary fusion of single crystals. The TEM image of the positive electrode active material is shown in FIG. 3C. FIG. 3C further shows that the particle morphology of the positive electrode active material is a fusion formed by at least partially fused primary single crystal particles. The SEM image of the cross section of the positive electrode active material is shown in FIG. 3D. FIG. 3D more clearly shows that the particle morphology of the positive electrode active material is a fusion formed by at least partially fused primary single crystal particles.

[0082] In a preferred embodiment, the primary single crystal particles have an average size of about 0.2-3 μm and the secondary amalgamations of single crystals have an average particle size of about 0.5-15 μm. According to the present application, the average particle size can be determined by dynamic light scattering.

[0083] In a preferred embodiment, the positive electrode active material has characteristic diffraction peaks at about 18.6°, about 36.5°, and about 44.3° in an X-ray diffraction pattern. The ratio of the intensity of the diffraction peak at 2θ of about 18.6° to the intensity of the diffraction peak at 2θ of about 44.3° is about 1.5 or more, more preferably about 1.7 or more. The intensity of the diffraction peak is calculated as the height of the diffraction peak.

[0084] In a preferred embodiment, as shown in FIG. 4, the diffraction peaks of the positive electrode active material are very sharp, indicating that the crystal structure of the positive electrode active material is well developed. The diffraction pattern shows no impurity peaks, indicating that the purity of the positive electrode active material is relatively high. In the X-ray diffraction pattern of the positive electrode active material shown in FIG. 4, characteristic diffraction peaks exist at 2θ of about 18.6°, about 36.5°, and about 44.3°, respectively. The ratio of the intensity of the diffraction peak at 2θ of about 18.6° to the intensity of the diffraction peak at 2θ of 44.3° is about 1.8. And the diffraction peak at 2θ of about 65° is clearly split, indicating that the positive electrode active material has a good layered crystal structure.

[0085] In a fifth aspect, the present application provides a method for producing a method for manufacturing a semiconductor device comprising: A method for producing a lithium battery positive electrode active material, comprising the steps of: (I) preparing a lithium battery positive electrode active material precursor; (II) mixing the precursor with a lithium source to cause a solid-state reaction to obtain a positive electrode active material; Including, The precursor is a lithium battery positive electrode active material precursor according to the first or third aspect of the present application.

[0086] According to the fifth aspect of the present application, the characteristics of the lithium battery positive electrode active material precursor prepared in step (I) are as described in the first or third aspect of the present application, and therefore, description thereof will be omitted here.

[0087] In a preferred embodiment, step (I) further comprises preparing a lithium battery positive electrode active material precursor according to the method for preparing a lithium battery positive electrode active material precursor as described in the second aspect of the present application. In this preferred embodiment, the features of the method for preparing a lithium battery positive electrode active material precursor are as described in the second aspect of the present application, and therefore will not be described here.

[0088] During research, the present inventors unexpectedly found that when a precursor including an aggregate of plate-like single crystals and polyhedral single crystal particles according to the present application is used in the preparation of a positive electrode active material, or when a positive electrode active material precursor is prepared by intermittently supplying a metal salt solution, the final positive electrode active material obtained has a special morphology, and the particle morphology of the positive electrode active material is a secondary fusion of single crystals formed by at least partially fused primary single crystal particles, and the special morphology imparts improved electrochemical properties to the positive electrode active material.

[0089] The lithium source used in the present application is not particularly limited and may be any of various lithium sources conventionally used in the preparation of ternary positive electrode active materials for lithium batteries. In a preferred embodiment, the lithium source used in step (II) is at least one selected from the group consisting of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, and lithium acetate.

[0090] In a more preferred embodiment, the molar ratio of the lithium source to the precursor, calculated as metal element, is about 0.9:1 to about 1.2:1, for example, about 0.9:1, about 1.0:1, about 1.1:1, and about 1.2:1, or within a range formed between any two of these ratios.

[0091] In the present application, the mixing in step (II) is not particularly limited as long as the lithium source and the lithium battery positive electrode active material precursor can be uniformly mixed, such as by ball milling, shearing, grinding, blending, etc. Preferably, the mixing time is about 1 to 4 hours.

[0092] In the present application, the solid-state reaction described in step (II) may be carried out by any conventional method used in the art to prepare lithium battery positive electrode active materials.

[0093] In a preferred embodiment, the solid-state reaction is carried out by calcining the mixture of the precursor and the lithium source. The calcination may be carried out by a conventional method, and is not particularly limited in the present application.

[0094] In a further preferred embodiment, the baking treatment comprises a first baking and a second baking.

[0095] The conditions for the first firing preferably include a firing temperature of about 300 to 600°C (e.g., about 300°C, about 350°C, about 400°C, about 450°C, about 500°C, about 550°C, about 600°C, or a range formed between any two of these values, more preferably a firing temperature of about 450 to 550°C) and a firing time of about 1 hour to about 10 hours (e.g., a firing time of about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, and about 10 hours, or a range formed between any two of these values, and more preferably a firing time of about 4 hours to about 8 hours).

[0096] The second firing conditions preferably include a firing temperature of about 650 to 1000°C (e.g., a firing temperature of about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, about 900°C, about 950°C, and about 1000°C, or within a range formed between any two of these values, and more preferably, a firing temperature of about 750 to 900°C) and a firing time of about 4 hours to about 48 hours (e.g., a firing time of about 4 hours, about 8 hours, about 12 hours, about 16 hours, about 20 hours, about 24 hours, about 28 hours, about 32 hours, about 36 hours, about 40 hours, about 44 hours, and about 48 hours, or within a range formed between any two of these values, and more preferably, a firing time of about 8 hours to about 24 hours).

[0097] In a preferred embodiment, the rate of the temperature increase step for increasing the temperature to the first baking temperature and the second baking temperature is not particularly limited, but is preferably about 0.5 to 10° C. / min, for example, about 0.5° C. / min, about 1° C. / min, about 2° C. / min, about 3° C. / min, about 5° C. / min, about 10° C. / min, or within a temperature range formed between any two of these values.

[0098] In the present application, it is preferred to employ a multi-step firing process including a first firing and a second firing to obtain improved electrochemical properties. Alternatively, a single firing may be performed immediately under the conditions used in the second firing, which may also result in good electrochemical properties.

[0099] In a sixth aspect, the present application provides a positive electrode active material obtainable by the method for producing a positive electrode active material for a lithium battery described above.

[0100] The characteristics of the lithium battery positive electrode active material according to the sixth aspect of the present application are as described in the fourth aspect of the present application, and therefore a description thereof will be omitted here.

[0101] In a seventh aspect, there is provided the use of a lithium battery cathode active material precursor or cathode active material according to the present application in the preparation of a lithium battery cathode.

[0102] Methods for preparing a lithium battery positive electrode using a lithium battery positive electrode active material precursor or a positive electrode active material are known in the art, and a detailed description thereof is omitted here.

[0103] In an eighth aspect, the present application provides a lithium battery cathode comprising an active cathode material, a binder, and a conductive additive, the active cathode material being as described in the fourth or sixth aspect of the present application.

[0104] In the present application, the conductive assistant and the binder may be various conductive assistants and binders conventionally used in the present technical field. For example, the conductive assistant may be acetylene black, carbon nanotubes, graphene, conductive polymers, etc. The binder may be polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, etc. Detailed description of these will be omitted. The amount of the conductive assistant and the binder may be any amount conventionally used in the present technical field. For example, the mass content of the positive electrode active material may be about 50 to 98%, the mass content of the conductive assistant may be about 1 to 25%, and the mass content of the binder may be about 1 to 25% relative to the total amount of the positive electrode.

[0105] In the present application, the lithium battery positive electrode may be prepared by various methods known to those skilled in the art, without particular limitation, and may be selected by those skilled in the art as needed. For example, in some embodiments, the positive electrode active material, the conductive additive, and the binder may be uniformly mixed, coated, and sliced ​​to prepare the lithium battery positive electrode.

[0106] In a ninth aspect, the present application provides a lithium battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator, the positive electrode being the lithium battery positive electrode of the eighth aspect of the present application.

[0107] In the present application, the negative electrode, electrolyte, and separator may be those conventionally used in lithium batteries, and are not particularly limited in the present application. For example, the negative electrode may be selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, mesophase microspheres, silicon, silicon / carbon composite, lithium, etc. The electrolyte may be selected from the group consisting of liquid electrolytes, gel electrolytes, solid electrolytes, etc. The separator may be selected from the group consisting of polyethylene separators, polypropylene separators, polyethylene / propylene composite separators, polyimide separators, etc.

[0108] In some preferred embodiments, the present application provides the following technical solutions: 1. A precursor of a positive electrode active material, It contains aggregates of plate-like single crystals and polyhedral single crystal particles, The X-ray diffraction patterns I(001), I(100), and I(101) of the precursor of the positive electrode active material are The relationship I(001) / I(100) is 1.5 or more, and I(001) / I(101) is 1.2 or more. The positive electrode active material precursor is Ni x Co y M z (OH)2, where M is at least one selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al; 1. A precursor, characterized in that 0.3≦x≦1, 0≦y≦0.5, and 0≦z≦0.3. 2. A method for producing a positive electrode active material precursor, comprising: (1) intermittently adding dropwise a metal salt solution, a precipitant solution, and optionally a complexing agent solution to mix and react; (2) subjecting the product obtained in the step (1) to solid-liquid separation and drying to obtain the positive electrode active material precursor; Including, The metal salt solution contains metal elements Ni, Co, and M, where M is at least one selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al; The production method, wherein the molar ratio of the Ni element, the Co element and the M element is (0.3-1):(0-0.5):(0-0.3), and the molar amounts of Co and M used are not zero. 3. The metal salt solution contains, as the metal elements, a combination of Ni, Co, and Mn, or a combination of Ni, Co, and Al; Preferably, the metal salt solution comprises at least one metal salt selected from the group consisting of metal sulfates, metal nitrates, metal acetates, and metal oxalates; Preferably, the metal salt solution has a concentration of 0.01 to 5 mol / L in terms of metal element. 4. The precipitating agent is at least one selected from the group consisting of NaOH, KOH, and LiOH; Preferably, the precipitant solution has a concentration of 0.02 to 10 mol / L. 5. The complexing agent is at least one selected from the group consisting of an ammonium ion donor, an ethanolamine complexing agent, an aminocarboxylic acid complexing agent, a hydroxyaminocarboxylic acid complexing agent, and a carboxylate complexing agent; Preferably, the complexing agent solution has a concentration of 0.01 to 15 mol / L. 6. The intermittent addition step of the step (1) is (1) simultaneously dropping the metal salt solution, the precipitant solution, and optionally the complexing agent solution into a reaction kettle under reaction conditions; (2) after the simultaneous dropping of the three solutions for 2 to 12 hours, interrupting the supply of the metal salt solution for 0.5 to 4 hours; (3) repeating the intermittent dropwise addition of step (2) until the reaction is complete; 6. The method according to any one of items 2 to 5, comprising: 7. The reaction conditions in the step (1) include a temperature of 30 to 70° C., preferably 45 to 60° C., and a reaction time of 10 hours or more, preferably 24 to 72 hours; Preferably, the mixing is carried out under stirring, More preferably, the stirring speed is 50 to 1000 r / min. 8. A precursor of a positive electrode active material obtained by the production method defined in any one of items 1 to 7 above. 9. A cathode active material precursor according to any one of items 1 to 8, comprising a lithium element and Preferably, the molar ratio of the lithium element to the positive electrode active material precursor is 0.9 to 1.2:1 in terms of metal element. 10. Use of the positive electrode active material precursor according to item 1 or 8, or the positive electrode active material according to item 9, in a lithium battery. 11. Having the morphology of secondary fusions of single crystals formed by at least partially fused primary single crystal particles; LiNi X Co y M z O2, in which M is at least one selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al, and the positive electrode active material satisfies 0.3≦x≦1, 0≦y≦0.5, and 0≦z≦0.3. 12. The positive electrode active material according to item 11, wherein the primary single crystal particles have a size of 0.2 to 3 μm and / or the secondary fused mass of single crystals has an average particle size of 0.5 to 1.5 μm. 13. A method for producing a positive electrode active material, comprising: (1) intermittently dropping a metal salt solution, a precipitant solution, and an optional complexing agent solution to mix and react with each other to obtain a precursor; (2) mixing the precursor obtained in the step (1) with a lithium source and subjecting the mixture to a solid-state reaction to obtain the positive electrode active material; Including, The metal salt solution contains the metal elements Ni, Co, and M, M is at least one selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al; A production method, characterized in that the molar ratio of Ni element, Co element and M element used is (0.3-1):(0-0.5):(0-0.3), and the molar amounts of Co and M used are not zero. 14. The intermittent addition step in the step (1) is (1) simultaneously dropping said metal salt solution, said precipitant solution, and optionally said complexing agent solution into a reaction kettle under reaction conditions; (2) after the simultaneous dropping of the three solutions for 2 to 12 hours, interrupting the supply of the metal salt solution for 0.5 to 4 hours; (3) repeating the intermittent dropwise addition of step (2) until the reaction is completed; 14. The method according to claim 13, comprising: 15. The reaction conditions in the step (1) include a reaction temperature of 30 to 70° C. and a reaction time of 10 hours or more; Preferably, the reaction is carried out under stirring. Item 14. The method according to item 13, wherein the stirring speed is more preferably 50 to 1000 rpm. 16. In the step (2), the solid-phase reaction is carried out by calcining a mixture of the precursor and the lithium source; Preferably, the firing process includes a first firing and a second firing, More preferably, the first firing conditions include a temperature of 300 to 600° C. and a firing time of 1 to 10 hours, and / or the second firing conditions include a firing temperature of 650 to 1000° C. and a firing time of 4 to 48 hours. 17. The metal salt solution contains, as metal elements, a combination of Ni, Co, and Mn, or a combination of Ni, Co, and Al; Preferably, the metal salt solution comprises at least one metal salt selected from the group consisting of metal sulfates, metal nitrates, metal acetates, and metal oxalates; 17. The method according to any one of items 13 to 16, wherein the metal salt solution has a concentration of 0.01 to 5 mol / L in terms of metal element. 18. The precipitating agent is at least one selected from the group consisting of NaOH, KOH, and LiOH; 17. The method according to any one of items 13 to 16, wherein the precipitant solution has a concentration of 0.02 to 10 mol / L. 19. The complexing agent is at least one selected from the group consisting of an ammonium ion donor, an ethanolamine complexing agent, an aminocarboxylic acid complexing agent, a hydroxyaminocarboxylic acid complexing agent, and a carboxylate complexing agent; 17. The method according to any one of items 13 to 16, wherein the complexing agent solution has a concentration of 0.01 to 15 mol / L. 20. The lithium source is at least one selected from the group consisting of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, and lithium acetate; 17. The method according to any one of items 13 to 16, wherein a molar ratio of the lithium source to the precursor is 0.9 to 1.2:1 in terms of metal element. 21. A positive electrode active material obtained by the method according to any one of items 13 to 20. 22. A positive electrode comprising a positive electrode active material, a binder, and a conductive additive; The positive electrode active material is a positive electrode active material defined in any one of items 11, 12, or 21; Preferably, the lithium battery positive electrode contains 50 to 98% by weight of the positive electrode active material, 1 to 25% by weight of the binder, and 1 to 25% by weight of the conductive assistant. 23. Use of the positive electrode active material as defined in any of paragraphs 11 and 12, or paragraph 21, or the lithium battery positive electrode as defined in paragraph 22, in a lithium battery. [Example] The present application will now be described in detail with reference to examples.

[0109] In the examples and comparative examples of this application, scanning electron microscope (SEM) images were obtained by a ZEISS Merlin scanning electron microscope manufactured by ZEISS Co., Ltd., Germany.

[0110] In the examples and comparative examples of this application, X-ray diffraction (XRD) patterns were measured by a D8 Advance SS X-ray diffractometer from Bruker Corporation, Germany.

[0111] In the examples and comparative examples of this application, the transmission electron microscope (TEM) images were obtained by a FEI Titan Cubed Themis G2 300 spherical aberration corrected transmission electron microscope from Thermo Fisher, USA. The sample preparation process for the transmission electron microscope is as follows: a small amount of powder sample is added to an ethanol solvent, ultrasonically dispersed at a power of 140 W for 15 minutes, the supernatant is aspirated and dropped onto a copper mesh, the copper mesh is dried to remove the solvent, and then the sample is placed in a sample bottle for observation.

[0112] In the examples and comparative examples of the present application, the compositions of the precursor and the positive electrode active material were measured by a Varian 725ES inductively coupled plasma spectroscopy (ICP-OES) from Agilent Technologies, USA.

[0113] In the examples and comparative examples of the present application, the method for preparing a cross-sectional sample of the positive electrode active material is as follows: The positive electrode active material, carbon black, and PVDF (binder) were uniformly mixed in a mass ratio of 90:5:5, and the resulting mixture was applied onto aluminum foil and vacuum dried at 80°C for 6 hours to obtain a pole piece containing the positive electrode active material. The pole piece was then cut using a clean blade, and the cut pole piece was attached to a sample stage and treated in a triple ion beam cross-sectional mode using an accelerating voltage of 5 kV for 2 hours to obtain a flat and clean cross-section for observation under a scanning electron microscope.

[0114] The metal salt solutions used in the following Examples and Comparative Examples are all sulfate solutions. [Example 1] The examples are provided to illustrate the preparation and evaluation of the positive electrode active material precursor and positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A metal salt solution with a metal ion concentration of 2 mol / L (molar ratio of nickel, cobalt, and manganese elements was 8:1:1) was prepared, a NaOH solution with a concentration of 4 mol / L was prepared, and an ammonia aqueous solution with a concentration of 6 mol / L was prepared.

[0115] The prepared metal salt solution, NaOH solution, and aqueous ammonia solution were simultaneously dropped into a reaction vessel, and the precipitation reaction was carried out while stirring. The dropping rate of the metal salt solution was 60 mL / h, and the dropping rate of the aqueous ammonia solution was 60 mL / h, and the pH value of the reaction system was controlled to 11 by adjusting the dropping rate of the NaOH solution. After dropping these three solutions simultaneously for 6 hours, the supply of the metal salt solution was interrupted for 1 hour while maintaining the supply of the NaOH solution and the aqueous ammonia solution, and the above process was repeated.

[0116] In the reaction process, the stirring speed was controlled at 600 rpm, the reaction temperature at 55° C., and the reaction time at 48 hours. After natural cooling, the precipitation reaction was stopped, and the obtained slurry was vacuum filtered and washed three times with deionized water, and then dried and dehydrated in a vacuum drying oven at 120° C. for 12 hours to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.799:0.100:0.101. SEM images of the obtained positive electrode active material precursor are shown in Figures 1A and 1B. As can be seen from Figures 1A and 1B, the morphology of the obtained positive electrode active material precursor is clearly different from that of conventional spherical polycrystalline aggregates, and consists of an aggregate of plate-like single crystals and polyhedral single crystal particles.

[0117] The X-ray diffraction pattern of the positive electrode active material precursor is shown in FIG. 2. The diffraction peaks of the positive electrode active material precursor are very sharp, indicating that the crystal structure of the positive electrode active material precursor is well grown. The intensities of the diffraction peaks corresponding to the (001) crystal plane and the (101) crystal plane are relatively high, and in particular, the intensity of the diffraction peak corresponding to the (001) crystal plane is obviously higher than the intensities of other diffraction peaks, indicating that the (001) crystal plane and the (101) crystal plane of the positive electrode active material precursor, especially the (001) crystal plane, are more fully exposed. The intensity ratio of I(001) / I(100) is 2.45, the intensity ratio of I(001) / I(101) is 1.45, and the intensity ratio of I(101) / I(100) is 1.69. (3) Preparation of positive electrode active material 10 g of the positive electrode active material precursor was collected, and a lithium source LiOH·H2O was added so that the molar ratio of Li:(Ni+Co+Mn) was 1.02:1. The resulting material was ball milled for 2 hours, mixed uniformly, and then loaded into a crucible and fired in multiple stages at high temperatures. In the first firing stage, the temperature was raised from room temperature to 450°C at a rate of 5°C / min and maintained for 6 hours. In the second firing stage, the temperature was raised from 450°C to 850°C at a rate of 5°C / min and maintained for 12 hours. The resulting material was then naturally cooled to obtain a positive electrode active material. (4) Evaluation of positive electrode active material SEM images of the positive electrode active material are shown in FIG. 3A and FIG. 3B. As can be seen from FIG. 3A and FIG. 3B, the particle morphology of the positive electrode active material is a secondary fusion of single crystals formed by at least partially fused primary single crystal particles. The average size of the primary single crystal particles of the positive electrode active material is 0.2-3 μm, and the average particle size of the secondary fusion of single crystals is 0.5-15 μm. A TEM image of the positive electrode active material is shown in FIG. 3C. As can be clearly seen from FIG. 3C, after the ultrasonic dispersion treatment in the sample preparation process, the particle morphology of the positive electrode active material still maintains the state of a fusion formed by at least partially fused primary single crystal particles. A SEM image of a cross section of the positive electrode active material is shown in FIG. 3D. As can be more visually and clearly seen from FIG. 3D, the primary single crystal particles fuse with each other and grow together to form particles in the form of secondary fusion.

[0118] The X-ray diffraction pattern of the positive electrode active material is shown in FIG. 4. The diffraction peak of the positive electrode active material is very sharp, indicating that the crystal structure of the positive electrode active material is well grown. In addition, since there is no impurity peak in the X-ray diffraction pattern, it can be seen that the purity of the positive electrode active material is high. In the X-ray diffraction pattern of the positive electrode active material, characteristic diffraction peaks exist at 2θ of about 18.6°, about 36.5°, and about 44.3°, respectively. The ratio of the intensity of the diffraction peak at 2θ of about 18.6° to the intensity of the diffraction peak at 2θ of about 44.3° is 1.8. At 2θ of about 65°, the diffraction peak is clearly split, indicating that the positive electrode active material has a good layered crystal structure.

[0119] The electrochemical properties of the positive electrode active material were evaluated as follows. 10 g of the positive electrode active material was taken, and 1.25 g of acetylene black and 12.5 g of a 10% mass fraction polyvinylidene fluoride solution (solvent: N-methylpyrrolidone) were added and mixed uniformly. The mixture was applied and sliced ​​to obtain a positive electrode piece. A lithium piece was used as the negative electrode, and a liquid electrolyte consisting of a solute, a solvent, and an additive was used as the electrolyte. The solute was 1.2 M LiPF6, the solvent was a mixed solvent of EC, DEC, and DMC in a volume ratio of 1:1:1, and the additive was VC with a concentration of 1.5 wt %. A commercially available Celgard 2325 diaphragm (USA) was used as a separator, and the above components were assembled in a glove box to form a lithium battery. The electrochemical properties of the lithium battery were evaluated. The charge and discharge curves measured at a rate of 0.1 C are shown in FIG. 5. The charge-discharge curves show that the material has a specific charge capacity of 224.6mAh / g, a specific discharge capacity of 206.9mAh / g, and a first cycle efficiency of 92.1%. The cycle stability curves measured at a rate of 1C are shown in Figure 6. The cycle stability curves show that the material has a capacity retention rate of 96.1% after 80 cycles, and therefore has excellent cycle stability. The output characteristic results are shown in Figure 7, which show that the material has a maximum discharge capacity of about 120mAh / g even at a high rate of 10C.

[0120] The results of discharge capacity, first cycle efficiency, and capacity retention after 80 cycles are shown in Table 3. [Example 2] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A metal salt solution with a metal ion concentration of 2 mol / L (molar ratio of nickel, cobalt, and manganese elements was 18:1:1) was prepared, a NaOH solution with a concentration of 4 mol / L was prepared, and an aqueous ammonia solution with a concentration of 6 mol / L was prepared.

[0121] The prepared metal salt solution, NaOH solution, and ammonia aqueous solution were simultaneously dropped into a reaction vessel while stirring to carry out a precipitation reaction. The dropping rate of the metal salt solution was 60 mL / hour, the dropping rate of the ammonia aqueous solution was 60 mL / hour, and the dropping rate of the NaOH solution was adjusted to control the pH value of the reaction system to 11. After dropping these three solutions simultaneously for 6 hours, the supply of the metal salt solution was interrupted for 1 hour while maintaining the supply of the NaOH solution and the ammonia aqueous solution, and the above process was repeated.

[0122] In the reaction process, the stirring speed was controlled at 600 rpm, the reaction temperature at 55° C., and the reaction time at 48 hours. After natural cooling, the precipitation reaction was stopped, and the obtained slurry was vacuum filtered and washed three times with deionized water, and then dried and dehydrated in a vacuum drying oven at 120° C. for 12 hours to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.903:0.048:0.049. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.37, the intensity ratio of I(001) / I(101) was 1.48, and the intensity ratio of I(101) / I(100) was 1.60. (3) Preparation of positive electrode active material 10 g of the positive electrode active material precursor was collected, and a lithium source LiOH·H2O was added so that the molar ratio of Li:(Ni+Co+Mn) was 1.02:1. The resulting material was ball milled for 2 hours, mixed uniformly, and then loaded into a crucible and fired in multiple stages at high temperatures. In the first firing stage, the temperature was raised from room temperature to 500°C at a rate of 10°C / min and maintained for 4 hours. In the second firing stage, the temperature was raised from 500°C to 750°C at a rate of 10°C / min and maintained for 8 hours. The resulting material was then naturally cooled to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0123] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 3] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A metal salt solution with a metal ion concentration of 2 mol / L (molar ratio of nickel, cobalt, and manganese elements was 3:1:1) was prepared, a NaOH solution with a concentration of 4 mol / L was prepared, and an aqueous ammonia solution with a concentration of 6 mol / L was prepared.

[0124] The prepared metal salt solution, NaOH solution, and ammonia aqueous solution were simultaneously dropped into a reaction vessel while stirring to carry out a precipitation reaction. The dropping rate of the metal salt solution was 60 mL / hour, the dropping rate of the ammonia aqueous solution was 60 mL / hour, and the dropping rate of the NaOH solution was adjusted to control the pH value of the reaction system to 11. After dropping these three solutions simultaneously for 6 hours, the supply of the metal salt solution was interrupted for 1 hour while maintaining the supply of the NaOH solution and the ammonia aqueous solution, and the above process was repeated.

[0125] In the reaction process, the stirring speed was controlled at 600 rpm, the reaction temperature at 55° C., and the reaction time at 48 hours. After natural cooling, the precipitation reaction was stopped, and the obtained slurry was vacuum filtered and washed three times with deionized water, and then dried and dehydrated in a vacuum drying oven at 120° C. for 12 hours to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.602:0.201:0.197. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.59, the intensity ratio of I(001) / I(101) was 1.22, and the intensity ratio of I(101) / I(100) was 1.30. (3) Preparation of positive electrode active material 10 g of the precursor was collected, and the lithium source LiOH·H2O was added so that the molar ratio of Li:(Ni+Co+Mn) was 1.02:1. The resulting material was ball milled for 2 hours, mixed uniformly, and then loaded into a crucible and fired at high temperature in multiple stages. In the first firing stage, the temperature was raised from room temperature to 550°C at a rate of 3°C / min and maintained for 8 hours. In the second firing stage, the temperature was raised from 550°C to 900°C at a rate of 3°C / min and maintained for 24 hours. The resulting material was then naturally cooled to obtain the positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0126] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 4] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A metal salt solution with a metal ion concentration of 3 mol / L (molar ratio of nickel, cobalt, and manganese elements was 8:1:1) was prepared, a NaOH solution with a concentration of 8 mol / L was prepared, and an aqueous ammonia solution with a concentration of 10 mol / L was prepared.

[0127] The same procedure as in Example 1 was carried out to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.797:0.098:0.105. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.98, the intensity ratio of I(001) / I(101) was 1.42, and the intensity ratio of I(101) / I(100) was 1.39. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0128] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 5] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A metal salt solution with a metal ion concentration of 0.5 mol / L (molar ratio of nickel, cobalt, and manganese elements was 8:1:1) was prepared, a NaOH solution with a concentration of 2 mol / L was prepared, and an ammonia aqueous solution with a concentration of 2 mol / L was prepared.

[0129] The same procedure as in Example 1 was carried out to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.802:0.101:0.097. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.87, the intensity ratio of I(001) / I(101) was 1.39, and the intensity ratio of I(101) / I(100) was 1.35. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0130] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 6] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A metal salt aqueous solution with a metal ion concentration of 5 mol / L (molar ratio of nickel, cobalt, and manganese elements was 8:1:1) was prepared, a NaOH solution with a concentration of 10 mol / L was prepared, and an ammonia aqueous solution with a concentration of 15 mol / L was prepared.

[0131] The same procedure as in Example 1 was carried out to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.801:0.099:0.100. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.77, the intensity ratio of I(001) / I(101) was 1.33, and the intensity ratio of I(101) / I(100) was 1.33. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0132] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 7] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A metal salt solution with a metal ion concentration of 0.01 mol / L (molar ratio of nickel, cobalt, and manganese elements was 8:1:1) was prepared, a NaOH solution with a concentration of 0.02 mol / L was prepared, and an aqueous ammonia solution with a concentration of 0.01 mol / L was prepared.

[0133] The same procedure as in Example 1 was carried out to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.799:0.103:0.098. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.71, the intensity ratio of I(001) / I(101) was 1.29, and the intensity ratio of I(101) / I(100) was 1.33. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0134] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 8] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same operation as in Example 1 was carried out except that the pH of the reaction system was controlled to 12 by adjusting the dropping rate of the NaOH solution during the dropping step, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.797:0.102:0.101. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.65, the intensity ratio of I(001) / I(101) was 1.25, and the intensity ratio of I(101) / I(100) was 1.32. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0135] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 9] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same operation as in Example 1 was carried out except that the pH of the reaction system was controlled to 9 by adjusting the dropping rate of the NaOH solution during the dropping step, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.791:0.105:0.104. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.68, the intensity ratio of I(001) / I(101) was 1.26, and the intensity ratio of I(101) / I(100) was 1.33. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0136] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 10] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same operation as in Example 1 was carried out except that the reaction temperature during the dropping step was controlled to 70° C., to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.800:0.098:0.102. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.86, the intensity ratio of I(001) / I(101) was 1.38, and the intensity ratio of I(101) / I(100) was 1.35. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0137] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 11] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same operation as in Example 1 was carried out except that the reaction temperature during the dropping step was controlled to 30° C., to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.805:0.102:0.093. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.02, the intensity ratio of I(001) / I(101) was 1.44, and the intensity ratio of I(101) / I(100) was 1.40. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0138] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 12] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same procedure as in Example 1 was carried out except that the reaction time was changed to 12 hours, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.792:0.104:0.104. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.81, the intensity ratio of I(001) / I(101) was 1.38, and the intensity ratio of I(101) / I(100) was 1.31. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0139] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 13] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same operation as in Example 1 was carried out except that the stirring speed was set to 50 rpm, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.789:0.108:0.103. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 1.62, the intensity ratio of I(001) / I(101) was 1.24, and the intensity ratio of I(101) / I(100) was 1.31. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0140] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 14] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same operation as in Example 1 was carried out except that the stirring speed was set to 1000 rpm, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.800:0.100:0.100. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.41, the intensity ratio of I(001) / I(101) was 1.51, and the intensity ratio of I(101) / I(100) was 1.60. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0141] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 15] This example is provided to illustrate the preparation and evaluation of positive electrode active materials according to the present application. (1) Preparation of positive electrode active material A positive electrode active material was obtained by carrying out the same operations as in Example 1, except that in the first stage of the multi-stage firing, the temperature was raised from room temperature to 600° C. at a rate of 5° C. / min and maintained for 1 hour, and in the second stage, the temperature was raised from 600° C. to 750° C. at a rate of 5° C. / min and maintained for 48 hours. (2) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0142] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 16] This example is provided to illustrate the preparation and evaluation of positive electrode active materials according to the present application. (1) Preparation of positive electrode active material A positive electrode active material was obtained by carrying out the same operations as in Example 1, except that in the first stage of the multi-stage firing, the temperature was raised from room temperature to 300° C. at a rate of 5° C. / min and maintained for 10 hours, and in the second stage, the temperature was raised from 300° C. to 1000° C. at a rate of 5° C. / min and maintained for 4 hours. (2) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0143] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 17] The examples are provided to illustrate the preparation and evaluation of positive electrode active materials according to the present application. (1) Preparation of positive electrode active material The same procedure as in Example 1 was carried out, except that a single-stage calcination was carried out in which the temperature was raised from room temperature to 850° C. at a rate of 5° C. / min and maintained for 12 hours, to obtain a positive electrode active material. (2) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0144] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 18] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same procedure as in Example 1 was carried out except that a KOH solution of the same concentration was used as the precipitant, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.799:0.101:0.100. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B and an X-ray diffraction pattern similar to that in Figure 2, with the intensity ratios of I(001) / I(100) being 2.43, I(001) / I(101) being 1.51, and I(101) / I(100) being 1.61. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0145] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 19] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same procedure as in Example 1 was carried out except that a diethanolamine solution of the same concentration was used as the complexing agent, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.792:0.105:0.103. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.42, the intensity ratio of I(001) / I(101) was 1.58, and the intensity ratio of I(101) / I(100) was 1.53. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to Figures 3A and 3B, and a TEM image similar to Figure 3C.

[0146] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 20] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A positive electrode active material precursor was obtained in the same manner as in Example 1, except that a disodium ethylenediaminetetraacetate solution having the same concentration was used as the complexing agent. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.805:0.097:0.098. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.43, the intensity ratio of I(001) / I(101) was 1.55, and the intensity ratio of I(101) / I(100) was 1.57. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to Figures 3A and 3B, and a TEM image similar to Figure 3C.

[0147] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 21] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A positive electrode active material precursor was obtained in the same manner as in Example 1, except that a sodium citrate solution of the same concentration was used as the complexing agent. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.800:0.102:0.098. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.43, the intensity ratio of I(001) / I(101) was 1.54, and the intensity ratio of I(101) / I(100) was 1.58. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to Figures 3A and 3B, and a TEM image similar to Figure 3C.

[0148] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 22] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A positive electrode active material precursor was obtained in the same manner as in Example 1, except that the metal salt solution was a 2 mol / L solution containing nickel, cobalt, and aluminum in a molar ratio of 8:1.5:0.5. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Al in the obtained positive electrode active material precursor was 0.802:0.153:0.045. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.44, the intensity ratio of I(001) / I(101) was 1.53, and the intensity ratio of I(101) / I(100) was 1.59. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to Figures 3A and 3B, and a TEM image similar to Figure 3C.

[0149] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 23] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor A positive electrode active material precursor was obtained in the same manner as in Example 1, except that the metal salt solution was a 2 mol / L solution containing nickel, cobalt, and magnesium in a molar ratio of 8:1:1. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni, Co, and Mg in the obtained positive electrode active material precursor was 0.801:0.102:0.097. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.44, the intensity ratio of I(001) / I(101) was 1.55, and the intensity ratio of I(101) / I(100) was 1.57. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0150] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 24] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor Further, the same procedure as in Example 1 was carried out except that 0.02 mol / L of TiSO4 was added to the metal salt solution, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn:Ti in the obtained positive electrode active material precursor was 0.795:0.101:0.104:0.009. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.32, the intensity ratio of I(001) / I(101) was 1.49, and the intensity ratio of I(101) / I(100) was 1.56. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to Figures 3A and 3B, and a TEM image similar to Figure 3C.

[0151] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 25] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same procedure as in Example 1 was carried out except that 0.01 mol / L of Cr2(SO4)3 was added to the metal salt solution, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn:Cr in the obtained positive electrode active material precursor was 0.798:0.103:0.099:0.011. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.29, the intensity ratio of I(001) / I(101) was 1.47, and the intensity ratio of I(101) / I(100) was 1.56. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to Figures 3A and 3B, and a TEM image similar to Figure 3C.

[0152] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 26] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same procedure as in Example 1 was carried out except that 0.02 mol / L of Fe(NO3)3·9H2O was added to the metal salt solution, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn:Fe in the obtained positive electrode active material precursor was 0.803:0.096:0.101:0.010. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.26, the intensity ratio of I(001) / I(101) was 1.47, and the intensity ratio of I(101) / I(100) was 1.54. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0153] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 27] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same procedure as in Example 1 was carried out except that 0.02 mol / L of CuSO4·5H2O was further added to the metal salt solution, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn:Cu in the obtained positive electrode active material precursor was 0.801:0.100:0.099:0.009. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.09, the intensity ratio of I(001) / I(101) was 1.45, and the intensity ratio of I(101) / I(100) was 1.44. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0154] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Example 28] This example is provided to illustrate the preparation and evaluation of a positive electrode active material precursor and a positive electrode active material according to the present application. (1) Preparation of positive electrode active material precursor The same procedure as in Example 1 was carried out except that 0.02 mol / L of ZnSO4·H2O was further added to the metal salt solution, to obtain a positive electrode active material precursor. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn:Zn in the obtained positive electrode active material precursor was 0.797:0.104:0.099:0.010. The positive electrode active material precursor showed SEM images similar to those in Figures 1A and 1B, and an X-ray diffraction pattern similar to that in Figure 2. The intensity ratio of I(001) / I(100) was 2.13, the intensity ratio of I(001) / I(101) was 1.46, and the intensity ratio of I(101) / I(100) was 1.46. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The cathode active material exhibits SEM images similar to FIGS. 3A and 3B, and a TEM image similar to FIG. 3C.

[0155] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1, and the results of the discharge capacity, the first cycle efficiency, and the capacity retention rate after 80 cycles are shown in Table 3. [Comparative Example 1] This comparative example is provided to illustrate the preparation and evaluation of cathode active material precursors and cathode active materials not according to the present application. (1) Preparation of positive electrode active material precursor The same operation as in Example 1 was performed to obtain a positive electrode active material precursor, except that the dropping step was a continuous dropping step of the metal solution, the precipitant solution, and the complexing agent solution, and there was no intermittent dropping step of the metal solution. (2) Evaluation of the positive electrode active material precursor The molar ratio of Ni:Co:Mn in the obtained positive electrode active material precursor was 0.799:0.102:0.099. An SEM image of the obtained positive electrode active material precursor is shown in Figure 8. It can be seen that the morphology of the positive electrode active material precursor is a spherical polycrystalline aggregate having a good sphericity.

[0156] The X-ray diffraction pattern is shown in Figure 9. It can be seen that the difference between the (001) crystal plane, the (100) crystal plane, and the (101) crystal plane is small, and the intensity ratio of I(001) / I(100) is 1.19, the intensity ratio of I(001) / I(101) is 1.04, and the intensity ratio of I(101) / I(100) is 1.14. (3) Preparation of positive electrode active material The same procedure as in Example 1 was carried out to obtain a positive electrode active material. (4) Evaluation of positive electrode active material The SEM image of the cathode active material is shown in Figure 10A. The morphology of the obtained cathode active material is found to be secondary micrometer spherical polycrystalline aggregates with good sphericity formed by nanometer or submicrometer primary particles.

[0157] A TEM image of the positive active material is shown in Figure 10B. As can be seen from Figure 10B, after ultrasonic treatment during the sample preparation process, the second-order micrometer spherical polycrystalline aggregates of the positive active material partially collapse to produce separate individual nanoparticles.

[0158] The electrochemical characteristics of the positive electrode active material were evaluated in the same manner as in Example 1. The results of the discharge capacity, first cycle efficiency, and capacity retention after 80 cycles are shown in Table 3, and the results of the output characteristics are shown in FIG.

[0159] [Table 1]

[0160] JPEG0007601866000002.jpg33169

[0161] [Table 2]

[0162] JPEG0007601866000004.jpg33169

[0163] [Table 3]

[0164] JPEG0007601866000006.jpg41169

[0165] The results compared with the comparative examples shown in Table 3 reveal the following: The lithium battery positive electrode active material precursor according to the present application, unlike a precursor having a morphology of spherical polycrystalline aggregates, includes aggregates of plate-like single crystals and polyhedral single crystal particles, and has a larger exposed area of ​​the (001) crystal plane and the (101) crystal plane. Meanwhile, unlike a spherical polycrystalline aggregate material and a dispersed single crystal particle material, the lithium battery positive electrode active material according to the present application is a particle material in the form of a secondary fusion of single crystals formed by at least partially fused primary single crystal particles, and has improved electrochemical properties such as higher discharge capacity and first cycle efficiency, and improved cycle performance.

[0166] The results of the power characteristics compared to the comparative example shown in Figures 7 and 11 reveal the following: The lithium battery positive electrode active material precursor and positive electrode active material according to the present application exhibit greatly improved power characteristics and exhibit significantly higher discharge capacity at high rates. For example, at a rate of 10C, the discharge capacity of the positive electrode active material prepared using the precursor material of the present application is about twice that of the positive electrode active material obtained in the comparative example.

[0167] The present application has been described in detail above with reference to its preferred embodiments, but is not limited thereto. Various modifications can be made to the technical solutions disclosed in the present application, including various combinations of technical features made in any suitable manner other than those disclosed herein, without departing from the gist of the present application, and these modifications and combinations should also be considered as part of the disclosure of the present application, and all fall within the scope of the present application. [Brief description of the drawings]

[0168] [Figure 1A] 1 is a SEM image of the positive electrode active material precursor obtained in Example 1 of the present application. [Figure 1B] 1 is a SEM image of the positive electrode active material precursor obtained in Example 1 of the present application. [Diagram 2] 1 shows an X-ray diffraction pattern of the positive electrode active material precursor obtained in Example 1 of the present application. [Figure 3A] 1 is an SEM image of the positive electrode active material obtained in Example 1 of the present application. [Figure 3B] 1 is an SEM image of the positive electrode active material obtained in Example 1 of the present application. [Figure 3C] 1 is a TEM image of the positive electrode active material obtained in Example 1 of the present application. [Figure 3D] 1 is an SEM image of a cross section of the positive electrode active material obtained in Example 1 of the present application. [Figure 4] 1 shows an X-ray diffraction pattern of the positive electrode active material obtained in Example 1 of the present application. [Diagram 5] 1 shows the charge / discharge curve of a lithium battery assembled using the positive electrode active material of Example 1 of the present application, measured at a rate of 0.1C. [Figure 6] 1 shows the cycle capacity retention curve of a lithium battery assembled using the positive electrode active material of Example 1 of the present application, measured at a rate of 0.1C. [Figure 7] 1 shows the capacity results measured at various ratios of a lithium battery assembled using the positive electrode active material of Example 1 of the present application. [Figure 8] 1 is a SEM image of a positive electrode active material precursor obtained in Comparative Example 1 of the present application. [Figure 9] 1 shows an X-ray diffraction pattern of the positive electrode active material precursor obtained in Comparative Example 1 of the present application. [Figure 10A] 1 is an SEM image of the positive electrode active material obtained in Comparative Example 1 of the present application. [Figure 10B] 1 is a TEM image of the positive electrode active material obtained in Comparative Example 1 of the present application. [Figure 11] 1 shows the capacity results measured at various ratios of a lithium battery assembled using the positive electrode active material of Comparative Example 1 of the present application.

Claims

1. A precursor of a lithium battery positive electrode active material, Ni x Co y M z (OH) 2 M is at least one metal selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al, 0.3≦x≦1, 0<y≦0.5, 0<z≦0.3, and the values ​​of x, y, and z satisfy the electroneutrality law; The precursor comprises an aggregate of plate-like single crystals and polyhedral single crystal particles, The X-ray diffraction pattern of the precursor has I(001), I(100), and I(101). I(001) / I(100) is 1.5 or more, and I(001) / I(101) is 1.2 or more; Fulfilling relationships, I(001), I(100), and I(101) represent the intensities at the peak heights of the diffraction peaks corresponding to the (001), (100), and (101) crystal planes, respectively, of the precursor.

2. 2. The precursor of claim 1, wherein M is at least one of Mn, Al, and Mg, or a combination of at least one of Mn, Al, and Mg with at least one selected from the group consisting of Fe, Cr, Cu, Ti, W, Mo, Nb, Zn, Sn, Zr, and Ga.

3. 2. The precursor of claim 1, wherein 0.6≦x≦0.95, 0.025≦y≦0.2, and 0.025≦z≦0.

2.

4. The X-ray diffraction pattern of the precursor has I(001), I(100), and I(101). I(001) / I(100) is 1.8 or more and 10 or less; I(001) / I(101) is 1.3 or more and 5 or less, and I(101) / I(100) is 1.5 or more and 5 or less; The precursor of claim 1 which satisfies the relationship:

5. A method for producing a precursor of a lithium battery positive electrode active material, comprising the steps of: (1) a step of mixing a metal salt solution with a precipitant solution and a complexing agent solution to react with each other, the step being to continuously supply the precipitant solution and the complexing agent solution to a reaction system while intermittently supplying the metal salt solution to the reaction system; (2) subjecting the product obtained in the step (1) to solid-liquid separation and drying to obtain the precursor; Including, The metals in the metal salt solution include Ni, Co, and M; The metal M is at least one selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al; the molar ratio of the metals Ni, Co, and M is (0.3-1):(0-0.5):(0-0.3); A method of preparation in which the molar amounts of Co and M used are non-zero.

6. 6. The method according to claim 5, wherein the metal M is at least one of Mn, Al, and Mg, or a combination of at least one of Mn, Al, and Mg and at least one selected from the group consisting of Fe, Cr, Cu, Ti, W, Mo, Nb, Zn, Sn, Zr, and Ga.

7. The metal salt is at least one selected from the group consisting of sulfates, nitrates, acetates, chlorides, and oxalates, and / or 6. The method according to claim 5, wherein the metal salt solution has a concentration of 0.01 to 5 mol / L in terms of metal element.

8. The precipitating agent is at least one selected from the group consisting of NaOH, KOH, and LiOH; and / or The method according to claim 5, wherein the precipitant solution has a concentration of 0.02 to 10 mol / L.

9. the complexing agent is at least one selected from the group consisting of ammonium ion donors, ethanolamine complexing agents, aminocarboxylic acid complexing agents, hydroxyaminocarboxylic acid complexing agents, and carboxylic acid complexing agents; and / or The method according to claim 5, wherein the complexing agent solution has a concentration of 0.01 to 15 mol / L.

10. 6. The method according to claim 5, wherein the reaction conditions in the step (1) include a temperature of 30 to 70° C., a reaction time of 10 hours or more, and a pH of 9 to 14, and the metal salt solution is supplied to the reaction system in at least two portions.

11. The method according to claim 10, wherein the mixing in step (1) is carried out under stirring at a speed of 50 to 1000 r / min.

12. The step (1) (1a) continuously supplying the metal salt solution, the precipitant solution, and the complexing agent solution to a reactor, and mixing and reacting them for 2 to 12 hours; (1b) interrupting the supply of the metal salt solution for 0.5 to 4 hours; (1c) repeating steps (1a)-(1b) until the reaction is complete; and The method of claim 5 further comprising:

13. Li a Ni x Co y M z O 2 wherein M is at least one metal selected from the group consisting of Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, Mn, and Al, and 0.9≦a≦1.2, 0.3≦x≦1, 0<y≦0.5, and 0<z≦0.3, and the values ​​of a, x, y, and z satisfy the law of electrical neutrality; A positive electrode active material for a lithium battery comprising a plurality of particles in the form of a secondary fusion of a plurality of single crystals formed by at least partially fused primary single crystal particles.

14. the primary single crystal particles have an average size of 0.2 to 3 μm; The average grain size of the secondary fusion of the single crystals is 0.5 to 15 μm; and the positive electrode active material has a layered crystal structure; The positive electrode active material according to claim 13, comprising one or more of:

15. 14. The positive electrode active material according to claim 13, wherein M is at least one of Mn, Al, and Mg, or a combination of at least one of Mn, Al, and Mg and at least one selected from the group consisting of Fe, Cr, Cu, Ti, W, Mo, Nb, Zn, Sn, Zr, and Ga.

16. 14. The positive electrode active material of claim 13, wherein 0.6≦x≦0.95, 0.025≦y≦0.2, and 0.025≦z≦0.

2.

17. A method for producing a lithium battery positive electrode active material, comprising the steps of: (I) preparing a precursor of a lithium battery positive electrode active material; (II) mixing the precursor with a lithium source to cause a solid-state reaction to obtain the positive electrode active material; Including, The method for producing the positive electrode active material for a lithium battery according to any one of claims 1 to 4, wherein the precursor is a precursor for the positive electrode active material for a lithium battery according to any one of claims 1 to 4.

18. The method according to claim 17, wherein the step (I) further comprises the step of producing a precursor of the lithium battery positive electrode active material by using the method according to any one of claims 5 to 12.

19. The method according to claim 17 , wherein the solid-state reaction in the step (II) is carried out by baking a mixture of the precursor and the lithium source.

20. The firing process includes a first firing and a second firing, The conditions of the first firing include a firing temperature of 300° C. to 600° C. and a firing time of 1 to 10 hours; 20. The method of claim 19, wherein the conditions of the second baking include a baking temperature of 650° C. to 1000° C. and a baking time of 4 to 48 hours.

21. The lithium source is at least one selected from the group consisting of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, and lithium acetate; and / or The method according to claim 17, wherein the molar ratio of the lithium source to the precursor is 0.9 to 1.2:1 in terms of metal element.

22. The positive electrode active material includes a binder and a conductive additive, The positive electrode of a lithium battery, wherein the positive electrode active material is the positive electrode active material of the lithium battery according to claim 13.

23. The lithium battery positive electrode of claim 22, comprising 50 to 98 weight percent of said positive electrode active material, 1 to 25 weight percent of said binder, and 1 to 25 weight percent of said conductive additive.

24. A positive electrode, a negative electrode, an electrolyte, and a separator, 23. A lithium battery, wherein the positive electrode is the lithium battery positive electrode of claim 22.

Citation Information

Patent Citations

  • Positive electrode material for lithium secondary batteries, rechargeable battery therewith and manufacturing process thereof

    JP2004006277A

  • Active material for nonaqueous electrolyte secondary battery, and its manufacturing method

    JP2008258160A

  • Positive active material for lithium secondary battery and its manufacturing method

    JP2009266712A

  • Positive electrode active material precursor for lithium secondary battery, positive electrode active material prepared using the same, and lithium secondary battery including positive electrode active material

    JP2012004097A

  • Active material for nonaqueous electrolyte secondary battery, manufacturing method thereof, electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2013182782A